2017
DOI: 10.1183/13993003.02221-2016
|View full text |Cite
|
Sign up to set email alerts
|

Inducible laryngeal obstruction: an official joint European Respiratory Society and European Laryngological Society statement

Abstract: Inducible laryngeal obstruction (ILO) describes an inappropriate, transient, reversible narrowing of the larynx in response to external triggers. ILO is an important cause of a variety of respiratory symptoms and can mimic asthma. Current understanding of ILO has been hampered by imprecise nomenclature and variable approaches to assessment and management. A task force of the European Respiratory Society (ERS) and European Laryngological Society (ELS) was thus set up to address this, and to identify research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
241
1
17

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(261 citation statements)
references
References 102 publications
(160 reference statements)
2
241
1
17
Order By: Relevance
“…2 Two patients in our series demonstrated supraglottic closure, which has been usually described in association with exercise provocation. 2 Two patients in our series demonstrated supraglottic closure, which has been usually described in association with exercise provocation.…”
Section: Ilomentioning
confidence: 57%
See 2 more Smart Citations
“…2 Two patients in our series demonstrated supraglottic closure, which has been usually described in association with exercise provocation. 2 Two patients in our series demonstrated supraglottic closure, which has been usually described in association with exercise provocation.…”
Section: Ilomentioning
confidence: 57%
“…1,2 Traditionally, the gold standard for diagnosis has been the demonstration on direct laryngoscopy of abnormal (hence paradoxical) adduction of the vocal folds during the respiratory cycle accompanying a symptomatic episode. It is an umbrella term for any triggered laryngeal obstruction occurring at either the supraglottic (arytenoid region, epiglottis or false vocal folds) and/or glottic (true vocal folds) level of the larynx and includes the condition also known as paradoxical vocal fold motion disorder (PVFM), or vocal cord dysfunction (VCD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous laryngoscopic exercise testing (CLE) may be performed to visualize the larynx during exercise. CLE testing has demonstrated that a large proportion of patients with symptoms suggestive of VCD may demonstrate supraglottic closure of the aryepiglottic folds [76]. The term Inducible Laryngeal Obstruction (ILO) has been proposed, to cover both glottic and supraglottic obstruction, induced by stimuli such as exercise (EILO) or external stimulants [76].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…This phenomenon, most commonly termed vocal cord dysfunction and more recently termed inducible laryngeal obstruction (ILO), is often misdiagnosed and mistreated as asthma . This may be explained by the lack of a robust, accepted diagnostic methodology …”
Section: Introductionmentioning
confidence: 99%